A Modernist Approach to the Novel of Under the Devil’s Umbrella - Tahereh Sadeghbayan; Reza Sadeghi Shahpar; Ghahreman Shiri (Matn/Pizhūhī-i Adabī, 2019)
The first manifestations of the widespread and coherent use of the modernist techniques in Persian fiction can be traced to the 1960s, and the works of those authors who mostly belonged to the circle “Isfahan Gathering”. Gradually, the modernist style became the prevailing trend in Persian fiction in the 1970s and 1980s. The focus was on mental events, the markedness of individuals, and the characters’ mentality and inner feelings which were all presented by using new narration techniques. Mohammad Ayyoubi was among the most prolific modernist authors of the 1970s who has used modernist narration techniques in his works, such as Under the Devil’s Umbrella. This study seeks to answer this key question: What elements and factors have marked this novel as a modernist work? It was concluded that the elements and factors which characterize the novel Under the Devil’s Umbrella as a modernist novel include the confusion and rupture in narration, the uncommon plot, the ambiguity and complexity of narration, the character’s emotional turbulence, loneliness, and alienation, the transformation of the conception of time, the flowing state of mind, and the poeticized prose.